Using health primes to reduce unhealthy snack purchases among overweight consumers in a grocery store - Papies, E K; Potjes, I; Keesman, M; Schwinghammer, S; van Koningsbruggen, G M (International Journal of Obesity, 2014)
Objective: Healthy-eating intentions of overweight individuals are often thwarted by the presence of attractive food temptations in grocery stores and the home environment. To support healthy-eating intentions, we tested the effectiveness of a simple health prime to reduce the purchases of energy-dense snack foods in a grocery store among overweight individuals. Design: This field experiment had a 2 (condition: health prime vs control) × 2 (weight status: overweight vs normal weight) between-participants design. Method: Customers of a grocery store were handed a recipe flyer that either contained a health and diet prime, or not. Participants’ weight and height, as well as their attention to and awareness of the prime during shopping, were assessed by means of a questionnaire. The purchase of unhealthy snack foods was assessed by means of the receipt. Results: Results showed that the health prime reduced snack purchases compared with the control condition among overweight and obese participants. When primed, overweight and obese participants bought almost 75% fewer snacks than when not primed. Additional analyses showed that although the prime worked only when customers paid initial attention to the flyer that contained the health prime, no conscious awareness of the prime during grocery shopping was necessary for these effects. Conclusion: These findings suggest that health priming can lead to healthier grocery shopping among overweight consumers, without relying on conscious awareness during shopping. This makes priming a highly viable intervention tool to facilitate healthy food choices. Such tools are especially relevant in the setting of grocery shopping, given that they have direct effects on eating in the home environment and thus for longer-term weight management.